Bilingual Instruction in SMAN Bali Mandara: Student's Perspective - Loviyani, Ni Putu Ayu Niya; Padmadewi, Ni Nyoman; Artini, Luh Putu (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research aimed to investigate 11th-grade students' perceptions regarding the utilization of bilingual instruction at SMAN Bali Mandara. Employing a qualitative approach, the researcher analyzed data obtained through questionnaires and interviews to gain deeper insights into student perspectives. Analysis revealed that the majority of responses clustered around central tendencies, with seven statements garnering over 80% agreement, while the remaining two statements received lower agreement rates of 46% and 42%, respectively. Overall, students expressed a positive view of bilingual instruction, viewing it as a beneficial tool for enhancing their learning experiences. Consequently, this study contributes to the understanding of the significance and effectiveness of bilingual instruction in language education, with the potential to improve students' language skills.